Preliminary Study on Citronella Soap Production in Getting Halal Certification in Malaysia - Mazita, Mokhtar; Fernando, Yudi; Azizan, Azit; Wan Khairul Anuar, Wan Abd Manan; Ida Rizyani, Tahir (2020)
This research is considered, as herbal industry in Malaysia. It’s social enterprising project. With JAKIM halal certification it confirming the success of the industry (SMEs).The purpose of this study is to get halal certification. How homemade soap can help poor or middle income people generate extra income especially with halal certification. Through JAKIM Halal certification the product can be exported to 56 OIC countries. The target on this research among Malaysian. This study can prove the most effective way of exporting product to OIC countries and to cut the gaps.